Inverse method for the analysis of instrumented impact tests of polymers - Pettarin, Valeria (2007)
Impact testing has become an important technique to determine the parameters associated with dynamic fracture of polymeric materials. These parameters are commonly calculated from the experimentally measured load versus time curves. However, these curves are not what theoretically should be used for this purpose, because the measured load is not equal to the load exerted on the tested specimen, load from which the mechanical performance of the material must be evaluated. The recorded load is corrupted by the other forces acting during the experimental run, which depend in part on the characteristics of the tester and in part on the properties and geometry of the tested material. In order to extract from the corrupted load the useful information, a simple model composed of springs, point masses, and viscoelastic elements is used. The model is employed to formulate an inverse problem from which the load on the specimen is obtained using the recorded load. The methodology is tested using simulated as well as experimental curves of different polymeric materials such as polypropylene homopolymer, mid-density polyethylene, and rubber toughened polymethylmetacrylate. The simulated curves demonstrate the validity of the inverse technique applied. The experimental curves confirm the methodology in a real situation.